The Effect of Pregnant Women's Nutritional Intake on Birth Weight of Babies in Coastal Areas - Yuliani Budiyarti; Wahyuni Anwar; Andi Nursiah; Ita Nur Itsna; Dian Mahendra Yusuf (International Journal of Health Sciences, 2025)
Fetal growth and development during pregnancy are significantly influenced by the quality of maternal nutritional intake. Inadequate nutritional intake can lead to low birth weight (LBW), which increases the risk of various health complications, including developmental disorders, infections, and chronic diseases in adulthood. Coastal areas have specific social, economic, and cultural characteristics that can influence maternal dietary patterns during pregnancy, such as limited access to nutritious food or a reliance on certain seafood. Therefore, this study aims to evaluate the effect of maternal nutritional intake on birth weight in coastal areas. This study used an observational design with a cross-sectional approach. The sample consisted of 100 pregnant women who gave birth at a coastal community health center during January–June 2025, taken using a purposive sampling method. Data on nutritional intake were collected through a questionnaire that measured the frequency, type, and variety of food consumed during pregnancy, while birth weight was obtained from medical records. Data analysis was performed using the Pearson correlation test to determine the relationship between nutritional intake and birth weight, and linear regression to assess the effect of nutritional intake on infant weight. The results of the study showed a significant positive correlation between maternal nutritional intake and birth weight (r = 0.62; p < 0.01). Mothers who consumed a balanced diet, including protein, complex carbohydrates, vitamins, and minerals, tended to give birth to babies with normal birth weight. Conversely, mothers with less balanced nutritional intake had a higher risk of giving birth to babies with low birth weight. These findings emphasize the importance of nutrition education and providing nutritious food for pregnant women, especially in coastal areas, to support maternal and infant health and reduce the risk of neonatal complications associated with low birth weight.